Democracy, education, and equality - Cambridge University Press; Bible Society of South Africa; Cambridge University Press; Bible Society of South Africa (Cambridge: Cambridge University Press, 2006)
Many believe that equality of opportunity will be achieved when the prospects of children no longer depend upon the wealth and education of their parents. This study investigates whether democracy through education may be used to generate equality among citizens.
Includes bibliographical references and index.
Adult
Keywords: Cambridge University Press; Critical world issues; Kabbala; Achievement; South Africa; Adult Non-Fiction